Mycobacterium aurum is Unable to Survive Mycobacterium tuberculosis Latency Associated Stress Conditions: Implications as Non-suitable Model Organism - Sood, Shivani (Indian J Microbiol, 2016)
Mycobacterium tuberculosis manages to remain latent in the human body regardless of extensive chemotherapy. Complete eradication of tuberculosis (TB) requires treatment strategies targeted against latent form of infection, in addition to the current regimen of antimycobacterials. Many in vitro and in vivo models have been proposed to imitate latent TB infection, yet none of them is able to completely mimic latent infection state of M. tuberculosis. Highly infectious nature of the pathogen requiring BSL3 facilities and its long generation time further add to complications. M. aurum has been proposed as an important model organism for high throughput screening of drugs and exhibits high genomic similarity with that of M. tuberculosis. Thus, the present study was undertaken to explore if M. aurum could be used as a surrogate organism for studies related to M. tuberculosis latent infection. M. aurum was subjected to in vitro conditions of oxygen depletion, lack of nutrients and acidic stress encountered by latent M. tuberculosis bacteria. CFU count of M. aurum cells along with any change in cell shape and size was recorded at regular intervals during the stress conditions. M. aurum cells were unable to survive for extended periods under all three conditions used in the study. Thus, our studies suggest that M. aurum is not a suitable organism to mimic M. tuberculosis persistent infection under in vitro conditions, and further studies are required on different species for the establishment of a fast growing species as a suitable model for M. tuberculosis persistent infection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12088-016-0564-x) contains supplementary material, which is available to authorized users.